The Potrait of PAI and Budi Pekerti’s Learning in Public School on Earth Minorty - Rusmayani, Rusmayani (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Muslims are the largest minority in Bali, this is evident from the number muslim students who attend public schools. But the number of Muslim students is inversely proportional to the availability of PAI and Budi Pekerti teachers. PAI and Budi Pekerti learning in public schools keeps various problems including SMP N8, SMP PGRI 2, SMP dan SMA Dharma Praja Badung, SMP Kristen Harapan Sesetan, and SMA NI Gianyar are public high schools that have similar problems, starting from the learning hours ineffective in the implementation of PAI learning, impermanent classrooms, unavailability of PAI teaching aids, Friday prayer time problems that still have class hours, teacher to student teacher ratios that are not fair, even there are some schools that do not have PAI teachers. This is quite alarming because the right of Muslim students to get PAI learning services has not been maximally obtained besides being vulnerable to the inclusion of radical understanding of school-age children if PAI and Budi Pekerti lessons are taught by non-religious teachers. The challenges involved in optimizing PAI and Budi Pekerti learning in public schools must be overcome by the opportunities available to obtain quality graduates and noble character